1983
DOI: 10.1111/j.1600-0870.1983.tb00214.x
|View full text |Cite
|
Sign up to set email alerts
|

The yearly averaged air temperature in Rome from 1782 to 1975

Abstract: Air temperature data of Rome are analysed to point out the variations caused by natural events and human activities. In particular, the influence of the growth of the city on the minimum average temperature is evident. I t is also found that the air temperature seems to be affected by the solar cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Finally, while in works dealt with air temperature analysis a visible effect of the urban growth on the minimum air temperature time series was detected (e.g. Dettwiller , 1970aDettwiller , , 1978Oke, 1979;Nkedirim et al 1981;Colacino and Rovelli, 1983;Katsoulis, 1985Katsoulis, , 1987, from Figure 10 the urban island effect is not evident on the precipitation amount which presents a pattern affected by the synoptic systems behaviour.…”
Section: K=-lmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, while in works dealt with air temperature analysis a visible effect of the urban growth on the minimum air temperature time series was detected (e.g. Dettwiller , 1970aDettwiller , , 1978Oke, 1979;Nkedirim et al 1981;Colacino and Rovelli, 1983;Katsoulis, 1985Katsoulis, , 1987, from Figure 10 the urban island effect is not evident on the precipitation amount which presents a pattern affected by the synoptic systems behaviour.…”
Section: K=-lmentioning
confidence: 99%
“…It must be stressed, however, that the connection between atmospheric phenomena and solar cycle is not generally accepted and is very controversial (Pittock, 1978). Concerning the precipitation behaviour two different findings exist: the first states that no relevant effect of 11-yr solar cycle is present in precipitation data, the second claims instead that the solar cycle disturbance is present (King, 1975;Pittock, 1983;Colacino and Rovelli, 1983;Vines, 1984;Colacino and Purini, 1986).…”
Section: Periodicities Of Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that, due to the very high levels of energy consumption and friction in cities, significant amount of waste heat is stored in the walls of buildings, streets, etc., which gets released during the night, thereby making the nights warmer. Colacino and Rovelli (1983), from an analysis of mean annual surface air temperatures in Rome during 1782 to 1975, found that the increasing trend in urban temperatures was more conspicuous in the minimum temperatures rather than in the maximum temperatures (see also, Colacino and Levagini, 1982). Local temperature is thus one of the major climatic elements to record the environmental changes brought about by industrialization and urbanization.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas [2] also have done the studies over United stated and states that annual mean temperature is increasing due to urbanization. His study was based on climate records for the period 1901-1984.One more study done over Rome for a period of 1782 -1975 also reveals that the effect is more on minimum temperature [3,4] This clearly indicates that Urban Heat island is one of the major cause for temperature change so in Indian context we are trying to study the change in temperature.…”
Section: Introduction:-mentioning
confidence: 99%